Smart City As An Implementation of E-Government in Indonesia - Yuli Tirtariandi El Anshori (Jurusan Ilmu Administrasi Negara, 2019)
This research is aimed at obtaining findings about public service through smart governance and smart mobility in Bandung city. Bandung city as one of the pilot-project cities in this program in Indonesia has initiated a number of efforts toward the concept of smart city. The main concept of smart city is sensing, understanding, and acting processes based on the use of information technology in the government (e-government). Besides, it was about to seek the city problems in real time, and then respond properly, so that those problems are immediately followed up. One of the efforts to realize smart governance and smart mobility is through the establishment of command room. This research employed qualitative approach. The informants were staffs of information commission officials in Bandung and Bandung citizensas the sample. The data collecting techniques were an in-depth interview, observation, and document analysis. The findings of this research indicated that the public service in Bandung city is experiencing improvement quantitatively and qualitatively after the implementation of smart governance and smart mobility in the smart city framework. All efforts in improving the public service are controlled in Bandung Command Center based on the ICT use. Recently, there have been about 150 applications of smart city system in Bandung that have been implemented through online mode. It covers the affairs on organizing ID card, checking the service license or permission, and monitoring the traffic jam and flood in which those can be done quickly and in real time. It is because of the direct relationship to Bandung Command Center. While, one of the constraints in implementing smart governance in Bandung city was there still lacks of adequate internet connection capacity in the implementation of online report system for the district heads. Regarding smart mobility, one of the constraints was the lack of availability on CCTV and security tools. Besides, the respondents complained on the lack of socialization about the implementation of online report system that has been implemented in Bandung government. The possible suggestions for the Bandung government are the concern to the needs of more mature planning toward the programs of smart governance and smart mobility, preparing the human resources, and providing supporting infrastructures.